Moderate renal impairment does not preclude the accuracy of 24‐hour urine normetanephrine measurements for suspected pheochromoctyoma. (18th March 2020) - Kline, Gregory A.; Boyd, Jessica; Leung, Alex A.; Tang, Andrew; Sadrzadeh, Hossein M.
Abstract: Objective: A 24‐hour urine nor/metanephrine (urine NM‐MN) measurements are a recommended first step in pheochromocytoma diagnosis. We hypothesized the presence of renal impairment (CKD) significantly confounds the results obtained in a urine NM‐MN collection, giving artificially lower measurements. Design: Retrospective review of a comprehensive laboratory database with all urine NM‐MN results from Southern Alberta from 2010 to 2018 (n = 15 505). After excluding high probability pheochromocytoma cases, results from patients with three levels of CKD (n = 796) were compared to those without CKD to determine the potential CKD effect. Patients: All patients having urine NM‐MN collection during the time period, irrespective of ordering physician or test indication. Measurements: Urine NM‐MN was measured by liquid chromatography‐tandem mass spectrometry and glomerular filtration rate determined within a median of 1.9 days, as estimated by CKD‐EPI equation. Results: In subjects with mild‐to‐moderate renal impairment, there was no continuous gradient between subnormal renal function and urine NM‐MN measures. When the estimated GFR was < 15 mL/min/m 2, the hypothesized effect on lowered urine NM‐MN became apparent. Conclusions: A 24‐hour urine NM‐MN measurement is unlikely to be affected by mild‐to‐moderate renal impairment and may be used as a reliable diagnostic test. With more advanced renal impairment, CKD‐specific reference ranges or an alternative test may be needed.